Association Between Routes of Tobacco Use and Hypertension Among Adult Rural People in Bangladesh: A Cross-Sectional Study - Shobhan Das; Tanmay Mandal; Robert Spurgeon; Md Hasibur Rahman; Queeneth Edwards; Amenah Qotineh; A.S.M. Mohiuddin; Rezwana Islam Rimi; Md. Mahfujur Rahman; Md. Masudur Rahman; Logan Cowan (Tobacco Use Insights, 2025)
Objective This study assessed the association between various routes of tobacco use and hypertension while exploring the roles of confounders and effect modifiers among the adult rural people of Bangladesh. Methods A cross-sectional study was conducted with a combination of open and closed-ended questionnaires. Data were collected from 496 adult rural patients during their doctor visits. All the data were analyzed using SAS 9.4 statistical software. Continuous variables were summarized as Means (M) and Standard Deviations (SD), and categorical variables were summarized as frequencies and proportions. Logistic regression model assessed associations with Odds Ratios (ORs) and 95% Confidence Intervals (95% CIs). Results Among the 496 participants, 50.8% were female, with an average age of 49.5 ± 11.8 years (M ± SD). 19/496 (3.83%) of inhaled smoker participants had hypertension. 58/496 (11.69%) of the chewing tobacco users were discovered to be hypertensive. The combined use of both inhalation and chewing tobacco was associated with higher odds of hypertension (OR = 1.27, 95% CI: 0.64-2.49), while inhalation tobacco was not (OR = 0.16, 95% CI: 0.05-0.53). Betel leaf use was prevalent among chewing tobacco users but did not significantly modify the association with hypertension. Age was identified as an independent variable that did not confound or modify the association between tobacco use and hypertension. Conclusion Together, inhalation and chewing of tobacco may increase hypertension risk, necessitating targeted public health interventions to curb its use among adult Bangladeshi rural populations. Nevertheless, we cannot establish temporality or causality from this study.